A quality improvement initiative on the use of psychotropic drugs in nursing homes in Flanders. Issue 3 (4th May 2017) - Azermai, Majda; Wauters, Maarten; De Meester, Dirk; Renson, Lisa; Pauwels, Danny; Peeters, Laurine; Warie, Hans; Petrovic, Mirko
Abstract : Introduction: Government-funded quality improvement projects aimed to reduce the high psychotropic medication use in Belgian long-term care settings. Design: A pilot project (2013–2014) with a pre–post and follow-up intervention design. Methods: Two nursing homes received three educational courses. In the intervention nursing home (INH) additionally, a transition towards person-centred care through professional support was applied. Drug use was recorded at baseline, after 10 months (post) and after 22 months (follow-up), and coded into the Anatomical Therapeutic Chemical classification. Results: At baseline, the INH residents' ( n  = 118) mean age at baseline was 82 years, with 71% females. The control nursing home residents' (CNH, n  = 275) mean age was 82.7 years, with 75% females. At baseline, mean drug use was 9 (range 1–21) and 8 (range 0–20), predominantly with a high proportion of psychotropic drug users of 73 and 65%, in INH and CNH respectively. At the time of post-measurement, only the proportion of hypno-sedative users decreased significantly in the INH (by 13%, p  = 0.048). No significant changes were found in the CNH. At time of the follow-up, the proportion of hypno-sedative (51% vs. 31%; p  = 0.005) and antidepressant users (42% vs. 25%, p  = 0.007) decreased significantly in the INH. The decrease of antipsychotic drug users was less distinct. In the CNH, the proportion of hypno-sedative, antidepressant and overall psychotropic drug users did not change significantly. Conclusion: This quality improvement initiative led to a significant decrease in the use of psychotropic drugs in the INH, even after 1-year follow-up. Education only had a limited effect.